Are masculine-faced CEOs linked to higher stock price risks? Evidence from Indonesia - Soeprajitno, Raden Roro Widya Ningtyas; Rahayu Putri Agustina; Izzul Islam Noor Mustain; Indra Wijaya Kusuma (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2024)
This study examines whether masculine-faced CEOs are associated with a higher stock price crash risk. Using the purposive sampling method, we collected 2,969 samples from companies listed on the Indonesia Stock Exchange from 2010 to 2019. We use the least square regression test with the robust Coarsened Exact Matching (CEM) approach to overcome sensitivity to behavioral bias. We found that CEOs with masculine faces are at higher risk of causing falling stock prices and are proven to be robust. Furthermore, only male CEOs with masculine faces were associated with falling stock prices; not female CEOs. Our findings are the first in Indonesia, complementing the development of the literature on individual characteristics by identifying CEOs with masculine faces as personality and characteristic shapers of falling stock prices. Although this study is limited to measuring facial features, which are part of an individual’s gene characteristics, it also provides stakeholders with insights into the importance of considering facial structure when evaluating CEO decision-making.